Temperatures for fertilization and hatching and their influence on determining the sex ratio of the silver catfish Rhamdia quelen - doi: 10.4025/actascibiolsci.v32i2.5261 - Longo, Ricardo da Silva (2010)
This study aimed to evaluate the effects of water temperature during fertilization and egg incubation in the determination of the sex ratio of fingerlings of silver catfish Rhamdia quelen. Water temperatures of 19, 25 and 30°C were used during the egg fertilizations, and the eggs were then incubated at temperatures of 19, 25 or 30°C for each fertilization temperature condition. An increase in temperature reduced the fertilization rate of R. quelen, while the final number of fish was reduced when a lower temperature was used during egg incubation. The temperatures of fertilization and incubation that were tested did not alter the sex ratio.